Antitumor activity and constituents of Jatropha curcas Linn - Oguntimein, Babajide Olanrewaju 1952-
The ethanolic extract of defatted leaves and twigs of Jatropha curcas Linn. has demonstrated antitumor activity against P-388 lymphocytic leukemia (PS), in both in vivo and in vitro systems. Fractionation of the ethanolic extract resulted in a number of active fractions. One of these active fractions was purified to a major spot by column and preparative thin layer chromatography. The major spot decomposed during the purification process as shown by thin layer chromatographic analyses. Other active fractions were also investigated. Column chromatographic analyses of the non-active fractions as well as the n-hexane extract gave nine known compounds: 1-Triacontanol, β-D-glucoside of β-sitosterol, mixture of β-sitosterol, stigmasterol and campesterol, &alpha-amyrin, 7-keto-β-sitosterol, 7-β-hydroxyl-β-sitosterol, and 7-α-hydroxyl-β-sitosterol.
Available to the general public.
Thesis (Master of Science in Pharmacognosy)--University of Mississippi, August 1977.
Keywords: Jatropha; Antineoplastic agents; Pharmacognosy; Euphorbiaceae